2015
DOI: 10.1089/ten.tea.2013.0597
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Cell Ingrowth, Proliferation, and Early Differentiation in a Three-Dimensional Silicon Carbide Scaffold Using Low-Intensity Pulsed Ultrasound

Abstract: Concerns over the use of autografts or allografts have necessitated the development of biomaterials for bone regeneration. Various studies have been performed to optimize the cultivation of osteogenic cells using osteoconductive porous scaffolds. The aim of this study was to evaluate the osteogenic efficiency of bone cell ingrowth, proliferation, and early differentiation in a silicon carbide (SiC) porous ceramic scaffold promoted with lowintensity pulsed ultrasound. MC3T3-E1 mouse preosteoblasts were seeded o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…Cellular infiltration inside PLGA, MWCNT and SWCNT scaffolds was assessed by image processing of confocal Z-stacks of calcein-AM stained MC3T3 cells [49]. Each individual stack was subjected to spectral-color coding steps to false color-code the cells as a function of Z-depth i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cellular infiltration inside PLGA, MWCNT and SWCNT scaffolds was assessed by image processing of confocal Z-stacks of calcein-AM stained MC3T3 cells [49]. Each individual stack was subjected to spectral-color coding steps to false color-code the cells as a function of Z-depth i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Image processing to assess cellular infiltration Cellular infiltration into PLGA, MWCNT, and SWCNT scaffolds was assessed by image processing of confocal Z-stacks of calcein-AM-stained MC3T3 cells. 49 Each individual stack was subjected to spectral color-coding steps to false color code the cells as a function of Z-depth, that is, cellular infiltration. Figure 9(A-C) show infiltration of cells on PLGA, MWCNT, and SWCNT scaffolds, respectively.…”
Section: Immunofluorescence Analysismentioning
confidence: 99%
“…The parameters of the in vitro porous Ti64 scaffolds are as follows: pore size of 400–500 µm, cylindrical block scaffolds 10 mm in diameter and 3 mm in height, and porosity of 65% to70% (Figure A). The parameters of the in vivo scaffolds are as follows: pore size of 800 μm to 1 mm, dimensions of 10 × 5 × 4 mm, and porosity of 80% (Figure B).…”
Section: Methodsmentioning
confidence: 99%
“…LIPUS resulted in shortening the overall bone healing time in several animal models and clinical trials . Recently, some studies have reported the effect of LIPUS on various cellular activities on porous scaffolds, such as cell proliferation, gene expression, collagen synthesis, and protein synthesis . However, these studies were all performed under the confined parameters of LIPUS.…”
mentioning
confidence: 99%
“…The enhanced mechanical properties were correlated to the microstructures of the nanoscaffold, which had ultrafine grains and increased density of solid matrix as a result of the enhanced neck growth of ceramic nanoparticles during the sintering process (Figure 3.10e vs. f). For example, in a recent study, osteogenic efficiency of bone cell ingrowth, proliferation, and early differentiation in a 3-D SiC porous ceramic scaffold with ultrasound treatment was studied [89]. 3-D porous SiC scaffolds have been fabricated and studied for potential applications in bone repair and regeneration.…”
Section: Nanoscaffoldsmentioning
confidence: 99%